Knowledge, attitudes and practices related to neglected tropical diseases (schistosomiasis and fascioliasis) of public health importance: A cross-sectional study - Riaz, Sajida; Ahmed, Haroon; Kiani, Sana Azeem; Afzal, Muhammad Sohail; Simsek, Sami; Celik, Figen; Wasif, Samia; Bangash, Nazneen; Naqvi, Syed Kamran; Zhang, Jing; Cao, Jianping (Frontiers in Veterinary Science, 2023)
Snails play an important role as an intermediate host in various parasitic diseases, which are referred to as snail-borne parasitic diseases (SBPDs). The prevalence of the SBPDs, schistosomiasis and fascioliasis is low in Pakistan compared to other countries. The present study investigated knowledge, attitudes, and practices related to these two SPBDs and risk factors associated with them among the humans living in close contact with livestock and pets from three regions of Pakistan: Punjab, Islamabad and Azad Jammu and Kashmir (AJK). A cross-sectional survey was conducted using a structured questionnaire to assess participants' knowledge, attitude and practices related to schistosomiasis and fascioliasis during 2021-2022. The majority of the 507 participants who were interviewed had good knowledge of schistosomiasis and fascioliasis: 43% were aware of schistosomiasis and 57% were aware of fascioliasis, but only 25% knew about snails as an intermediate host. Most respondents had a positive attitude towards treatment, prevention and control of the diseases but they did not have any healthcare facilities. This study underscores the importance of the public's awareness of the need to control SBPDs. It also draws attention to the need for health education for risk reduction and the prevention of SBPDs in endemic areas.